O jogo como recurso didático na apropriação dos números inteiros: uma experiência de sucesso - Soares, Pércio José (2008)
The purpose of this study was to investigate the possibility of reintroducing the negative whole numbers, from a teaching intervention focusing on problem solving, using games as teaching resources and, also, verifying the understanding from the students over the operations (adding and subtracting) with positive and negative whole numbers, from The work done with the textbook adopted by the school in which we did the research. For such, a interventionist research was done with students from three groups from the seventh grade (which used to be 6th grade) of Elementary school, from a private school in São Paulo: two groups constituted the experimental group (EG) and one constituted the control group (CG) The field research was divided in two steps: applying diagnostic tools (prior and after the tests)for the EG and the CG and applying the teaching intervention, using the game Winnings and Losses and the Surprise Ring Game only in the EG. From the theoretical point of view, Jean Piaget, Lino Macedo, Cecília Kimura, Julia Borin, Lara and Murcia s ideas were used as a support over games and knowledge acquisition. Results: the result analysis from the tests of the CG and E showed prior to the test that the students really had some knowledge over negative whole numbers. The groups results in relation to the tests showed that there was difference in the results and this indicates improvement with an evolution of 13.9% on EG, representing a growth of 20.3% in relation to the prior test. The CG showed an evolution of 13.7%, which represents a growth of 20.3% in relation to the prior test. Thus, the growth of the EG was higher than the one from the CG. However, both groups showed a greater difficulty in solving number expressions that involved negative whole numbers. As for the teaching intervention, it was observed that the games may contribute to the significant learning of negative whole numbers. This enabled the understanding of the ideas from the adding and subtracting operations by means of several relations established between student x game, student x classmates and student x researcher in a problem solving context